6,000 miles to freedom : two boys and their flight from the Taliban - Marchetti, Stéphane, 1978- (Graphic Mundi, 2022)
"A narrative account, in graphic novel format, of the traumatic experiences faced by children fleeing war and poverty in Afghanistan, as well as the isolation they often feel as refugees in the West"-- Provided by publisher.
"Originally published as 9603 Kilomètres: L'Odyssée de deux enfants, Futuropolis, Paris © 2020."
Keywords: Refugees -- Afghanistan -- Comic books, strips, etc.; Refugees -- England -- Comic books, strips, etc.; Refugee children -- Afghanistan -- Comic books, strips, etc.; Réfugiés -- Afghānistān -- Bandes dessinées.; Réfugiés -- Angleterre -- Bandes dessinées.; Enfants réfugiés -- Afghānistān -- Bandes dessinées.; Refugee children; Refugees; Afghanistan; England; Comics (Graphic works); Graphic novels; Graphic novels.